MODEL SISTEM INFORMASI MANAJEMEN KETAHANAN PANGAN (PEMANFAATAN DAN KETERSEDIAAN PANGAN) - -, Zaidir; -, Erizal (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2019)
The concept of food security considers the availability of food, access to food and the use of food as the main aspects supporting food security and linking these aspects to ownership of household assets, livelihood strategies, and political, social, institutional and economic environments. In Law Number 18 of 2012 it is said that the Government and Regional Government are obliged to develop, compile and develop a food information system on aspects of food utilization and availability. The benefits of information have a significant impact on an institution or the public. Quality information can only be produced from a quality information system. Data and information are needed as a basis for policy making and decisions from planning to evaluating activities. The model development method in this study is with the stages of analysis, design and coding and model testing. The results of this study are a model of the Food Security Information System that can provide information on food security analysis with various variations. Indicators of achievement in the study are in the form of design use case diagrams, database design and interface design.